A Socio-Pragmatic Study of Verbal and Nonverbal Acts Expressing Sympathy in the American Movie ‘The Help’ (مجلة ديالى للبحوث الانسانية, 2025)
Pragmatics studies speaker's meaning, considering social factors like gender, socioeconomic class, and age. It's essential to consider both form and function of language, as well as sociolinguistics when analyzing differences in social contexts. Sympathy is crucial in human life, as it helps individuals cope with problems and depression. The current study is concerned with the investigation and analysis of sympathy in the (the help) movie. This study is limited to an analysis of some paralinguistic acts that contain sympathy expressions. It aims at pinpointing out the forms of  the  speech acts used to express sympathy; investigating the paralinguistic acts associated with sympathy; and reveling the appropriateness of using the sympathetic acts in terms of the target social variables. The study has reached at some conclusions, among which is that the American movie writers tend to exploit commissive e and expressive speech acts in their effort of creating effective and moving sympathy situation, sympathy can be expressed verbally and nonverbally. Combining the paralinguistic acts, like gestures, eye contact, facial expressions, proxemics and tone with the verbal acts produce distinguished sympathy situations, and this is one of the excellent characteristic of the acted pieces of the literary works in comparison with other modes of communication, particularly those which are written to be read; effective and appropriate sympathy acts are highly influenced by the surrounding social variables like age, gender, ethnicity, position, and the like.     The model will analyze the possible socio-pragmatic interpretation entailed by the statements of sympathy, adopting Searle’s (1969) model for classifying the function of speech acts (representative, directives, expressive, declaratives, and commissives), some of paralinguistic acts, and the social variables of age, gender, position, ethnicity, and social class.